Abundance and symbiotic efficiency of indigenous rhizobia nodulating faba bean and common bean in southern Ethiopia - Tadele Geremu; Tadele Geremu; Girma Abera; Bekele Lemma; Frank Rasche (Frontiers in Soil Science)
The symbiotic association between legumes and indigenous rhizobia is crucial for enhancing legume productivity. However, inconsistent results and suboptimal performance of rhizobia inoculation in promoting legume production have been observed. In this regard, we assessed the abundance and symbiotic efficiency of indigenous rhizobia nodulating faba bean and common bean, as well as the soil factors affecting rhizobia abundance in southern Ethiopia. The study also compared the performance of indigenous rhizobia with commercial strains and mineral nitrogen treatment plants. A total of 132 soil samples were collected from barley, wheat, maize, potato, common bean, faba bean, intercropped common bean and maize, enset, and grazing land. Indigenous rhizobia were isolated and enumerated from these samples. Faba bean (FB) and common bean (CB) rhizobia population ranged from 0.0 to 1.7 x 104 and 1.7 x 101 to 1.7 x 107 cells g-1 soil, respectively. Rhizobia populations were significantly influenced by soil pH, EC, OC, TN, CEC, exchangeable acidity, aluminium, and the host crop occurrence. The isolated indigenous rhizobia demonstrated significant potential in enhancing nodulation, shoot dry weight, and TN accumulation in plants. Symbiotic efficiency indices revealed that over 95% of the indigenous rhizobia were effective in nodulation and shoot dry matter accumulation, indicating that naturally occurring rhizobia are efficient and may reduce the need for commercial inoculants in areas with abundant indigenous populations. However, in areas where rhizobia populations are low, strains isolated from faba bean (33FB, 84FB) and common bean (44CB, 102CB), which outperformed commercial strains should be further evaluated. The results suggest that soil rhizobia population levels should be assessed prior to inoculation to optimize nodulation and crop performance. To this end, it is emphasized to evaluate soil rhizobia strains to assess their stability and competitiveness relative to commercial inoculants across different agroecological conditions.